EFFECT OF VESTIBULAR STIMULATION ON BEHAVIORAL CHANGES IN PARKINSON DISEASE-INDUCED MICE - mohan, Ram; jayabal, Mohan; Ramanathan, Rashmi; shanmugam, Jeevithan; R, Archana (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: This prospective study was conducted to provide an authoritative database for beneficial effects of vestibular stimulation, a simple non-invasive method to alleviate the behavioral changes in Parkinson’s disease (PD). Methods: Vestibule is stimulated by caloric vestibular stimulation (CVS). Pesticide Rotenone is used to induce PD. Open field test and elevated plus maze were used to access learning, memory, and behavior. Results: Behavioral scores were taken before and after stimulation of the vestibular system. The scores were significantly different between rotenone-induced PD, control, and hot water vestibular stimulation groups (p<0.05). Conclusion: This study categorically confirms that CVS with hot water causes behavioral changes in PD. This study certainly merits further studies with higher sample sizes to confirm the effect of CVS for enhancement of learning, memory, and behavior in patients with Parkinsonism.